2014
DOI: 10.3389/fgene.2014.00358
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evolutionary diversity and phylogenetic structure across multiple forest dynamics plots: a mega-phylogeny approach

Abstract: Forest dynamics plots, which now span longitudes, latitudes, and habitat types across the globe, offer unparalleled insights into the ecological and evolutionary processes that determine how species are assembled into communities. Understanding phylogenetic relationships among species in a community has become an important component of assessing assembly processes. However, the application of evolutionary information to questions in community ecology has been limited in large part by the lack of accurate estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(106 citation statements)
references
References 55 publications
1
103
0
1
Order By: Relevance
“…As more DNA barcode data are assembled, an increased number of taxa will be woven into increasingly larger phylogenies. This approach results in more well-supported phylogenetic reconstructions of the constituent species from which individual community phylogenies may be pruned out for targeted analysis [35]. Furthermore, the use of a constraint tree derived from existing Tree of Life studies will enforce topological relations at deeper phylogenetic levels, where the limited signal from the small amount of nucleotide data provided by the DNA barcode markers is most problematic (Figure 3) [27].…”
Section: Idenɵficaɵon Of Crypɵc Life Stagesmentioning
confidence: 99%
See 2 more Smart Citations
“…As more DNA barcode data are assembled, an increased number of taxa will be woven into increasingly larger phylogenies. This approach results in more well-supported phylogenetic reconstructions of the constituent species from which individual community phylogenies may be pruned out for targeted analysis [35]. Furthermore, the use of a constraint tree derived from existing Tree of Life studies will enforce topological relations at deeper phylogenetic levels, where the limited signal from the small amount of nucleotide data provided by the DNA barcode markers is most problematic (Figure 3) [27].…”
Section: Idenɵficaɵon Of Crypɵc Life Stagesmentioning
confidence: 99%
“…The improvement of topological resolution through incorporation of DNA barcode data for all or most species in the community improves the power of evolutionary-based hypothesis testing in an ecological framework. Since that first DNA barcode-based community phylogeny, similar investigations have focused on other forests in the tropics [27,35]. A major challenge of reconstructing a phylogenetic tree using DNA barcode sequence data is to capture the proper evolutionary relations among both highly divergent as well as closely related species.…”
Section: Idenɵficaɵon Of Crypɵc Life Stagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular phylogenies were constructed for woody species in these FDPs using three barcode loci (rbcL, matK and trnH-psbA) (Kress et al 2009, Kress et al 2010, Pei et al 2011. In this study, we used a single dated mega-phylogeny that was constructed simultaneously based on the DNA barcode sequence data in different ForestGEO plots (Erickson et al 2014). Most species without…”
Section: Study Sites and Forest Plot Datamentioning
confidence: 99%
“…A unique challenge for plants is that plastid and nuclear DNA barcodes yield lower species resolution compared to the mitochondrial and nuclear barcodes used for animals and fungi (Naciri and Linder, 2015;Hollingsworth et al, 2016). However, building a geographically circumscribed reference library can improve the effectiveness of plant DNA barcoding (Clerc-Blain et al, 2010;Burgess et al, 2011;de Vere et al, 2012;Parmentier et al, 2013;Elliott and Davies, 2014;Erickson et al, 2014). Braukmann et al (2017a) recently showed that the discriminatory power of the most commonly used plant DNA barcodes (rbcL, matK, and ITS2) for the Canadian vascular plant species varies depending on the method of analysis (BLAST vs. Mothur) and biogeographic region (e.g., Canadian arctic vs. woodland).…”
mentioning
confidence: 99%